RETRACTED: Issues of identification in the technical term literary form interpretation - Xatamova Dilfuza; Boltaboev Hamidulla; Altundag M. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001